Relationship of excessive daytime sleepiness with bruxism, depression, anxiety, stress, and sex in odontology students – A cross sectional study - Turcio, Karina-Helga [UNESP] (2022)
Background: To verify if there is a correlation of excessive daytime sleepiness (EDS) with bruxism, depression, anxiety, stress, and sex in odontology students. Material and Methods: Four hundred dental students were selected. Students included in the study were those that were healthy, over 18 years old, and with similar weekly academic activities. Students excluded were those with temporomandibular disfunction, a high possibility of possessing obstructive sleep apnea and illnesses that cause EDS; along with smokers, users of illicit drugs, users of psychiatric medication, and those that abuse the consumption of alcohol. After the application of these criteria, 128 students were included in this study. EDS, bruxism, depression, anxiety, and stress were evaluated by the Epworth Sleepiness Scale, the Pintado et al. questionnaire, Beck Depression Inventory, Beck Anxiety Inventory, and the LIPP Adult Stress Symptom Inventory. Afterwards, the Spearman test (p< 0.05) was applied. Results: A high probability of EDS was present in 33.6% of the students. There was a positive correlation of EDS with females (Rank Correlation= 0.209; p= 0.018) and depression (Rank Correlation= 0.174; p= 0.049); between females and stress (Rank Correlation= 0.199; p= 0.024), and between females and anxiety (Rank Correlation= 0.178; p= 0.045). There was a positive correlation of bruxism with anxiety (Rank Correlation= 0.255; p= 0.004) and stress (Rank Correlation= 0.201; p= 0.023). There was no correlation of EDS with bruxism (p= 0.354), stress (p= 0.277), or anxiety (p= 0.114). There was no correlation of bruxism with females (p= 0.082) or depression (p= 0.362). Conclusions: A high probability of EDS was present in 33.6% of dentistry students, and there was a positive correlation of EDS with females and depression